Effects of additional neck cut of the femur on the range of motion in total hip arthroplasty for hip dislocation: a computer simulation study. Issue 1 (January 2022) - Makida, Kazuya; Seki, Taisuke; Osawa, Yusuke; Takegami, Yasuhiko; Higuchi, Yoshitoshi; Kusano, Taiki; Ishiguro, Naoki
Background: Subtrochanteric shortening osteotomy (SSO) is commonly performed in total hip arthroplasty (THA) for high hip dislocation. However, this procedure is technically difficult and includes complications. Additional neck cut (ANC) of the femur is a procedure that involves femoral shortening by possibly eliminating the need for SSO in THA for high hip dislocation. Herein, we evaluated the effect and the depth limit of ANC of the femur on the range of motion (ROM) in THA for high hip dislocation. Methods: ROM was measured in 26 patients with high hip dislocation using computer software. The stem was deeply positioned at 5-mm intervals from 0 mm to 30 mm (7 groups). The ROM before impingement was measured during flexion, internal rotation (IR) at 90° flexion, external rotation (ER) and abduction. Receiver operator coefficient (ROC) curves for abduction were generated. The cut-off value of ANC where the required ROM was achieved was also determined. Results: Deeper ANCs increased the ROM values during flexion and IR, but they decreased the ROM values during ER and abduction. The ROM values during ER were also limited in 0-mm ANCs. According to the result of the ROC curve for abduction, 15 mm was considered as the permissible range of ANC. Conclusions: In THA for high hip dislocation additional neck cut should be taken into consideration for hips requiring less than 15-mm shortening. For more extended corrections a subtrochanteric shortening osteotomy should be performed.